Interação genótipo x ambiente e variabilidade genética de caracteres agronômicos e qualidade de processamento em batata - Augustin, Lizete (2007)
Potato (Solanum tuberosum L) is an important crop plant and one of the most important food supplies in the world. There is an increasing market for processing potato in Brazil, and the expansion of the potato industry can only be sustained if good quality product supplies are available. The objectives of this work were: 1) to identify potato clones with high yield potential and industrial quality; 2) to access the influence of genotype by environment interaction on the expression of agronomic and processing quality traits of potato clones in order to determine the appropriate strategy in breeding potato for the target region of interest; 3) to study the genetic variability for agronomic and processing quality traits among clonal families developed at University of Passo Fundo, Passo Fundo-RS, Brazil; 4) to identify parental combinations that generate clones with superior genetic potential for breeding programs in the region; 5) to determine the effect of two growing seasons on the magnitude of genetics gains for the evaluated traits; 6) to evaluate if is possible to combine industrial tuber quality with agronomic traits to obtain superior quality clones with adaptation to North/Northeast region of Rio Grande do Sul. The work initiated in 2003, when nine cultivars and one clone developed at Federal University of Santa Maria were crossed. After in vitro multiplication at the Plant Biotechnology Laboratory of University of Passo Fundo (UPF), mini tubers were obtained and planted in the field in 2004. One-hundred seventy clones and the parents were grown at fall and spring growing seasons of 2006 at the UPF experimental field. The agronomics traits evaluated included yield traits, presence of deep eyes. The processing traits were evaluated at the Food Research Center (CEPA) of UPF and included dry matter content, reduced sugars contents and color chips. Heritability and genetic gain estimates were obtained for tuber number, mean tuber weight, plant yield and dry matter and correlation coefficients between traits. Evaluated traits included number of tubers per plant, tuber weight, plant yield, presence of deep eyes, dry matter content, reduced sugars content and chips color. Genotype x environment interaction (G x E) was analyzed for all traits. Reduced sugars and chip color were most influenced by growing season conditions. Genetic potential expression for yield traits was maximized in the spring season. Superior clones combining agronomic and quality traits were identified at the two growing seasons. High correlation between the two growing seasons was observed for the presence of deep eyes and dry matter, indicating they can be selected at either season. Genetic variability was observed for all agronomic and processing quality traits. Parental combinations as AtlanticxLady Roseta, SMIJ461-1x Atlantic and Catucha x Atlantic showed greater genetic gain potential and may be useful for potato breeding programs. Among processing quality traits, dry matter content showed the greatest herdability and for agronomics traits the greatest herdability was observed for presence of deep eyes. It was possible to combine good agronomics traits with high processing quality in potato and to obtain superior clones for the group of evaluated traits